GENERALIZED EQUATIONS OF MATHIEU - R.I. Parovik (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2011)
We consider a nonlocal model of the wave process, which generalizes the classical model parmetricheskogo resonance Mathieu. It is proved that this model has a unique solution.